Daily field checking list by Walter Rosene, December 20, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated December 20, 1936. This checklist was used by Walter Rosene to record birds sighted around North Bridge with Bob Walker between 8:15 and 10:15. Plustek--flatbed